Response of maize to nutrients sources in acidic soil of Upper Assam - Huchchappa Jamakhandi,; Shiva Dhar,; S.S. Rathore,; Sunil Mandi,; Lohit K. Baishaya,; Sudarshan S.,; Prakash Sonnad, (Annals of Agricultural Research, 2024)
The field study entitled “Response of maize to nutrients sources in acidic soil of upper Assam” was conducted during the kharif season of 2023 at the Experimental Farm of ICAR–Indian Agricultural Research Institute (IARI), Assam. The experiment was laid out in split plot design, replicated thrice and consists 3 organic supplements (Control, FYM @ 10 t ha-1 and Vermicompost @ 2.5 t ha-1) in mainplots and 4 inorganic nutrients management levels (Control + Lime @ 300 kg ha-1, 50 % RDF(NPK) + Lime @ 300 kg ha-1, 75% RDF(NPK) + Lime @ 300 kg ha-1 and 100% RDF(NPK)+Lime @ 300 kg ha-1) in sub plots. The experimental findings showed that among organic supplements, FYM @10 t ha-1 shows higher growth parameters, grain yield (4.37 t ha-1) and net returns (`71,040). The application of 10 t FYM ha-1 produced 4.29% and 32.42% more grain yield over 2.5 t vermicompost ha-1 (4.19t ha-1) and control(3.3t ha-1), respectively. Among inorganic nutrients management levels, 100% RDF(NPK)+Lime @ 300 kg ha-1 was superior in terms of crop growth, grain yield (4.43 ha-1) and more profitable (net B:C 1.7) compared to other levels. The 100% RDF (NPK) + Lime @ 300 kg ha-1 resulted in 5.23, 15.66 and 33.03 % more yield over 75% RDF(NPK) + Lime @ 300 kg ha-1 (4.21 t ha-1), 50% RDF (NPK) + Lime @ 300 kg ha-1 (3.83 t ha-1) and control + Lime @ 300 kg ha-1 (3.33 t ha-1), respectively.